Analysis of laboratory, clinical and radiological characteristics of patients with infectious spondylodiscitis - Milinković, Tea (Medicinski podmladak, 2025)
Introduction: Infective spondylodiscitis (IS) is a relatively rare disease characterized by nonspecific symptoms such as back pain and fever. Early diagnosis is difficult and often the disease is not immediately recognized despite the availability of radiological techniques such as magnetic resonance imaging (MRI) and computed tomography (CT). IS could have an acute, subacute or chronic course. Aim: The aim of the study is to analyze the laboratory, clinical and radiological characteristics of patients with IS, and to determine the diagnostic and therapeutic challenges. Material and methods: Data of patients suffering from IS and treated at the Clinic for Infectious and Tropical Diseases and Clinic for Orthopedics, University Clinical centre of Serbia were collected retrospectively. Laboratory, clinical, radiological and microbiological findings were analyzed, as well as the response to antimicrobial therapy. Results: 30 patients with equal representation of both sexes were included in the research. The most common microbiological isolates were Escherichia coli (E. coli) (6/19, 31.6%) and Staphylococcus aureus (S. aureus) (5/19, 26.3%). In the group of patients whose symptoms lasted ≥15 days before hospitalization, the average values ​​of the number of neutrophils were statistically significantly higher compared to the group of patients with an acute onset of the disease. The duration of hospitalization >4 weeks had a statistically significant effect on the onset of osteoporosis. Treatment with vancomycin and rifampicin from the beginning of hospitalization led to a statistically significantly shorter duration of hospitalization (≤4 weeks). Hospitalization was statistically significantly more likely to end in death in patients treated with empiric antibiotic therapy, and an unfavorable treatment outcome was recorded in 6 (20%) patients, and was not a consequence of IS complications. Conclusion: The length of hospital treatment depends on the clinical course of the disease, intensity of symptoms, type of microbiological isolate, antibiogram and control laboratory and radiographic findings. Keywords: spondylodiscitis, infection, vertebrae, antibiotics, therapy.